PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN MENURUNKAN TINGKAT KECEMASAN MATEMATIKA PESERTA DIDIK - Rahmat Hidayat; Ari Limay Trisno Putra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The meaningfulness of learning is determined by the form of learning presented by educators which affects the problem-solving ability and level of mathematical anxiety of students. The purpose of this study is to investigate to see an increase in problem-solving ability and reduce the level of mathematical anxiety of students in class VIII.A by applying an innovative problem-based learning (PBL) learning model. This research is a class action research (PTK). The study was conducted until and ended in the fourth cycle. The application of innovative problem-based learning models can improve problem-solving skills and reduce students' level of mathematical anxiety.Keyword: Problem Based Learning, Problem Solving Ability, AnxietÂ Abstrak: Kebermaknaan pembelajaran ditentukan oleh bentuk pembelajaran yang disajikan oleh Guru yang mempengaruhi kemampuan pemecahan masalah dan tingkat kecemasan matematis siswa. Tujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan pemecahan masalah dan penurunan tingkat kecemasan matematis siswa kelas VIII.A dengan menerapkan model pembelajaran inovatif berbasis masalah (PBL). Penelitian ini merupakan penelitian tindakan kelas (PTK). Penelitian ini dilaksanakan sampai dengan siklus IV. Penerapan model pembelajaran inovatif berbasis masalah dapat meningkatkan kemampuan pemecahan masalah dan menurunkan tingkat kecemasan matematis siswa.Kata kunci: Problem Based Learning, Problem Solving Ability, Anxiet